The use of Geographic Information System (GIS) and Remote Sensing (RS) for potential unconfined groundwater in structural and volcano landforms - Ihsan, Haikal Muhammad; Arrasyid, Riko; Darsiharjo, Darsiharjo; Ruhimat, Mamat (Geodesy and Cartography, 2023)
The Northern Bandung area covers two landforms, namely volcano and structural landforms. Unconfined groundwater has become the water source for local people’s daily needs in both landforms. It is necessary to map the potential unconfined groundwater for both volcano and structural landforms due to the significant role of springs for the local people living in those areas. This research aims to map the unconfined groundwater on the volcano and structural landforms. This study employed the approaches of Analytical Hierarchy Process (AHP), Geographic Information System (GIS), and Remote Sensing (RS) using the variables of lineament density, rainfall, slope, and Topographic Wetness Index (TWI), hydrogeology, drainage density, and land use. The result shows that each variable has the Consistency Ratio (CR) below 0,1, resulting in consistent research variables and appropriate for discussion. The classification of the potential groundwater is divided into three categories: low, medium, and high. The survey validation finds that 147 springs spread at 86 high lands, 55 medium lands, and six lowlands. This model can be an alternative to map the potential unconfined groundwater in both volcano and structural areas.